Route Optimization Of Mobile Medical Units Using Machine Learning And Maintaining Transparency In Pharmaceutical Supply Chain - Maheshwari, Shruti (IIT(BHU) Varanasi, 2023)
Abstract is available in the attachment.
Keywords: Mechanical Engineering